(untitled) (Fiep Bulletin - online, 2015)
This course was held at the National Institute of Physical Education, at Cruz Quebrada, 5 km. from Lisbon, on the mouth of the Tagus (the “sunny Coast”), and was attended by 150 teachers of physical education from Belgium, Canada, Spain, France, Italy, Portugal, Uruguay and Venezuela.